Measuring and weighing psychostasia in Q 6:37–38: Intertexts from the Old Testament - Howes, Llewellyn (HTS teologiese studies, 2014)
This article is the first of three on the relationship between the Sayings Gospel Q and the ancient concept of ‘psychostasia,’ which is the ancient notion that a divine or supernatural figure weighed people’s souls when judging them. The ultimate goal of all three articles is to enhance our understanding of Q 6:37–38, as well as of the Q document as a whole. In the current article, attention is focused on intertexts from the Old Testament, and the occurrences therein of the word ‘measure’ and the concept of ‘psychostasia’. The implications of these results for our interpretation of Q 6:37–38 are briefly noted. A second (future) article will focus on intertexts in apocryphal and pseudepigraphical writings from Second Temple Judaism dealing with ‘psychostasia’. A third study will ultimately spell out in more comprehensive detail the implications of the foregoing intertextual investigations on both our understanding of Q 6:37–38 and our understanding of the Sayings Gospel Q as a whole.